Pengaruh Katup Ekspansi Termostatik Dan Pipa Kapiler Terhadap Temperatur Dan Tekanan Pada Mesin Pendingin Siklus Kompresi Uap Menggunakan Refrigeran HCR-134A - Siregar, Izzuddin Ali Raja; Aziz, Azridjal; Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The basic functions of the expansion device in a refrigeration system is to reduce pressure from condenser pressure to evaporator pressure and regulate the refrigerant flow from the high pressure liquid line into the evaporator at a rate equal to the evaporation rate in the evaporator. In this study, the capillary tube and thermostatic expansion valves will be compared to determine the performance of each other. The experiment was conducted with using a vapor compression cycle testing device with HCR-134a refrigerant. The result shows that the average temperature on the testing points using thermostatic expansion valve is lower than the 1,25 m capillary tube except the temperature of compressor in and compressor out. Also the average pressure in the evaporator and condenser using thermostatic expansion valve is lower than 1,25 m capillary tube.Keywords : expansion device, temperature, pressure, HCR-134a